Juridical Analysis of Errors in Recording the Origin of Land on Land Management Rights by the National Land Agency - Josie Jayasaputra Kusmayadi; Benny Djaja (Dinasti Research, 2024)
Soil functions as the surface layer of the earth that supports plant roots' growth, supports upright plants and meets water and air needs. The importance of land for humans is very clear, because humans cannot live without land. Therefore, land registration becomes increasingly important for society as time goes by. The land registration process produces legal consequences, namely the issuance of a land certificate which functions as legal and strong evidence for the holder of rights to the land. However, with the large number of certificates issued by the National Land Agency (BPN), the possibility of errors in the certificate issuance process remains, even though the chance of such errors occurring is small. One error that may occur is an error in recording the origin of land over management rights, as illustrated in the Decision of the State Administrative Court for Judicial Review Number 206/PK/TUN/2023. This research uses normative juridical research methods. Errors or omissions in issuing a certificate can cause the certificate to become invalid, either due to inaccurate data on the legal subject or legal object stated in the certificate. These errors can occur at various stages of land registration. Adding phrases such as